Analisis Faktor yang Memengaruhi Niat Penggunaan Sistem Informasi Akuntansi - Kristiyanthi, Anak Agung Dwi; Dharmadiaksa, Ida Bagus (E-Jurnal Akuntansi; Vol 29 No 3 (2019), 2019)
Bank BPD Bali also play a role in driving the regional economy, especially in the Province of Bali by supporting development funding in the regions, including the service of Micro, Small and Medium Enterprises. However, there are several obstacles in implementing the system including limited time in completing work, the complexity of the latest system features so that employees are less controlled and experience is still inadequate. The number of samples in this study were 51 people. This study found that personalization and alternative attractiveness had a positive effect on perceived usefulness, alternative attractiveness had a positive effect on perceived ease of use, personalization had no effect on perceived ease of use and system user experience had no effect on both. Then the perception of usefulness has a positive effect on the intention to keep using, but does not affect the perception of ease of use. Keywords : Personalization; Alternative Attractiveness; System User Experience; SIA.